Soil Phosphorus Translocation via Preferential Flow Pathways: A Comparison of Two Sites With Different Phosphorus Stocks - Makowski, Vera; Julich, Stefan; Feger, Karl-Heinz; Julich, Dorit (Frontiers in Forests and Global Change, 2020)
Weather events where a dry period is followed by a heavy rainfall event appear to affect phosphorus (P) exports through preferential flow pathways from forest soils. Furthermore, the P stock of a site seems to influence the amount of exported P. To explore this, we installed zero-tension lysimeters in three trenches at two sites with contrasting soil P stocks. Lysimeters were installed in three different depths (topsoil, upper subsoil and deep subsoil) to explore P depth transport. We covered the forest floor above the lysimeters with tarpaulins to simulate a dry period and afterwards artificially irrigated the area. This experiment was repeated three times at each site. Lysimeter samples were analyzed for concentrations of total P, organic and inorganic dissolved P and particle bound P (> 0.45 µm). Loads of P and water flow rates were calculated. Results reveal differences between sites, events and depths. At both sites, concentrations and loads of P in the topsoil lysimeters were higher than in the subsoil lysimeters. This difference was particularly evident at the low P site and emphasized its nutrient recycling efficiency. Dissolved inorganic P showed clear peaks in the topsoil lysimeters, whereby in the subsoil, particle-bound P peaks were partly noticeable at both sites. Depth transport of P into the subsoil depended on initial soil moisture, soil texture and the spatial distribution of flow pathways. Further, we observed large heterogeneity within a single site, dependent on profile-specific characteristics. We conclude that under certain conditions, there is a depth transport of P into the subsoil and therefore a potential of P loss, especially for particle-bound P. Heterogeneity of the sites hampered the clear identification of effects and illustrated the need for further research with a specific focus on the role of soil heterogeneity.